A comparison of the efficacy of nystatin and fluconazole incorporated into tissue conditioner on the in vitro attachment and colonization of Candida Albicans - Abbas Falah-Tafti; Abbas Ali Jafari; Mohammad Hossein Lotfi-Kamran; Hossein Fallahzadeh; Reyhana Sadat Hayan (Dental Research Journal, 2010)
Background: Denture stomatitis is a common oral lesion following the use of ill-fitting dentures. A layer of tissue conditioner is usually used to improve adaptation of the denture. These liners can sup-port the in vivo adhesion and colonization of the oral Candida. The aim of this study was to evaluate the efficacy of the two common antifungal agents mixed with tissue conditioner against Candida al-bicans. Methods : Tissue conditioner disks (Acrosoft) with 5mm diameter and 1mm thickness containing dif-ferent concentrations of nystatin and fluconazole (1%, 3%, 5%, 10% wt/wt) as well as disks with no antifungal agents (8 disks for each group) were prepared for experimental biofilm formation by inocula-tion with Candida albicans cell suspensions. The specimens were incubated in cell culture microtiter plate wells containing Sabouraud′s broth in a rotator shaker at 30΀C for 48 hours. Then, the specimens were rinsed and sonicated in sterile water to remove surface organisms. The attached yeasts were enu-merated by inoculation of the yeast suspension on Sabouraud′s agar. The data was compared using Kruskal-Wallis and Dunn′s tests using prism software. P value less than 0.05 was considered signifi-cant. Results: The 1% to 10% mixture of nystatin and tissue conditioner completely inhibited the attach-ment and colonization of Candida albicans, although for fluconazole only a 10% concentration caused complete inhibition. Nystatin showed a potentially higher effect in inhibition of candida at-tachment and colonization (P = 0.0001) compared to that of fluconazole and a statistically significant difference was seen between 5% and 1% fluconazole (P = 0.0001). Conclusion : Tissue conditioner with 1% to 10% nystatin or 10% fluconazole can completely inhi-bit the adhesion and colonization of Candida albicans.